UJI DAYA TAHAN BEBERAPA BAHAN PEMBUNGKUS DALAM MENGENDALIKAN LALAT BUAH (Bactrocera spp.) PADA TANAMAN JAMBU BIJI (Psidium guajava L.) DI SENTRA PENGEMBANGAN PERTANIAN UNIVERSITAS RIAU - Candra, Dani; Sutikno, Agus; Salbiah, Desita (PEST Tropical Journal, 2013)
Fruit fly (Diptera : Tephritidae) are a major pest of guava plants which cansiderably lowers the production of fruits, both in guantity and guality. This studyaims to determine the durability of some packaging materials that are used tocontrol fruit flies in guava plants. This research was conducted at the Center forAgricultural Development and the University of Riau and Laboratory Plant PestFaculty Agricultural, from April to June 2013. This research was carried out byusing a randomized block design (RBD) with 5 treatments and 4 replication thenewsprint, black carbon paper, black plastic bags, cement paper, transparentplastic. The results of the study showed that the use of packaging materials thathold and effectively protect the guava fruit from treated paper material is cementweighing 151.450 g fruit, and fruit morphology yellowish green color, soft textureshape of a round and 51 days durability.Keyword: Guava (Psidium guajava L.), fruit fly (Bactrocera spp.), andpacking material